Valutazione di efficienza nella somministrazione dell’ormone della crescita (GH) - Spandonaro, Federico; Mancusi, Letizia (Farmeconomia. Health Economics and Therapeutic Pathways, 2013)
Treatment with growth hormone (somatropin) is effective in six different medical conditions: growth hormone deficiency (GHD), Turner syndrome (TS), growth retardation in children born small for gestational age (SGA), Prader-Willi syndrome (PWS), growth retardation due to chronic renal insufficiency (CRI), growth retardation associated with a deficiency of the gene SHOX (Short Stature HOmeoboXContaining gene). The treatment proved to be also effective in adults who have an impaired growth hormone (acquired in adulthood or childhood). The growth hormone (GH) is generally cost effective and, therefore, is usually reimbursed by public health services. In financial terms, GH is a major cost item for health systems. According to the Report OSMED 2010, GH ranks first in Italy between systemic hormonal preparations, excluding sex hormones, distributed by public system, with an annual value of approximately € 88 million (+ 12.7% compared to 2009). Considering the increasing need to control pharmaceutical expenditure, there is a strong interest for the efficient supply of the hormone by the regional health service. From this point of view, the comparison of the specialties on the market is normally carried out on the basis of the cost per mg; this approach, also used in the main studies of cost-effectiveness, is derived from a logic of cost minimization, but it may still be distorting, not taking into account the efficiency of devices used for the administration of the hormone. The proposed analysis verifies the efficiency of different available devices, evaluating the potential waste of product, depending both on the device used and on the characteristics of the population exposed to the treatment. Only in the case of single-dose and disposable formulations is theoretically possible to have zero waste and thus an equivalence between the actual cost of the treatment and the price charged. In other cases, the inefficiency causes a deviation between the actual cost and price. In the latter cases, since the theoretical amount of the population exposed to the treatment, it is estimated that the total share of potentially unused product can vary between 208,000 mg / year to 750,000 mg / year, depending on the device used. In particular, there is an actual average cost of treatment ranging between +9.9% and +11.4% of the ex-factory price; depending on the different doses and even between the different devices, the difference between the actual price and the theoretical price varies from a minimum of +6.9% and a maximum of +18.7%.